The association between Diastasis recti abdominis and pelvic floor dysfunction, sacroiliac joint dysfunction, and quality of life among postpartum women after Cesarean delivery - Saleh, Enas Abu; Walton, Lori; Said, Sahar; Raigangar, Veena; Kim, Meeyoung (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2023)
Purpose The goal of this study is to see if there's a predictive relationship between diastasis rectus abdominis and pelvic floor dysfunction, sacroiliac joint dysfunction, and postpartum women's health-related quality of life.Method This cross-sectional, correlative study focused on 32 postpartum mothers aged 18 to 45 years old. Real Ultrasound Sonographic Imaging (RUSI) was used to determine DRA. The Pelvic Floor Disability Index was used to assess pelvic floor dysfunction (PFDI). The Active Straight Leg Raise Test (ASLR), the Long Dorsal Sacral Ligament Test (LDL), and the Posterior Pelvic Provocation Test (P4) were also investigated. The Short Form-12 (SF-12) Survey was used to assess health-related quality of life (HRQoL).Results A negative correlation between DRA and postpartum period was recorded (ρ=0.0001). The following categories showed a significant positive correlation between DRA and Pelvic floor dysfunction: Pelvic Organ Prolapse Distress Inventory-6 (POPDI-6) corelated positively with DRA (ρ =0.01); Colorectal-Anal Distress Inventory-8 (CRAD-8) (ρ =0.02); Urinary Distress Inventory-6 (UDI-6) (ρ =0.00). There was no correlation between DRA and sacroiliac joint dysfunction (ρ =0.8).Conclusion DRA was discovered to be a strong predictor of pelvic floor dysfunction, such as prolapse, colorectal-anal dysfunction, and urine distress. There was no evidence of a link between DRA and sacroiliac joint dysfunction or HRQoL.
Keywords: Diastasis Recti Abdominis; Pelvic Organ Prolapse; pelvic floor dysfunction; Colorectal-Anal Distress; Urinary Distress; Real Ultrasound Sonographic Imaging